2021
DOI: 10.1089/neur.2021.0039
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Age and Biological Sex on Cerebrovascular Reactivity in Adult Moderate/Severe Traumatic Brain Injury: An Exploratory Analysis

Abstract: Age and biological sex are two potential important modifiers of cerebrovascular reactivity post-traumatic brain injury (TBI) requiring close evaluation for potential subgroup responses. The goal of this study was to provide a preliminary exploratory analysis of the impact of age and biological sex on measures of cerebrovascular function in moderate/severe TBI. Forty-nine patients from the prospectively maintained TBI database at the University of Manitoba with archived high-frequency digital cerebral physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 66 publications
3
8
2
Order By: Relevance
“…In an attempt to remedy this, the Winnipeg Acute TBI Laboratories performed an exploratory analysis that showed that there was a statistically significant relationship between PAx, RAC and age with linear regression and age trichotomization analysis but not with PRx and age. 16 Also, in their cohort, biological sex did not have an impact on the cerebrovascular reactivity measures. 16 This cohort had well controlled ICP and CPP values over the course of their intensive care unit (ICU) stay.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…In an attempt to remedy this, the Winnipeg Acute TBI Laboratories performed an exploratory analysis that showed that there was a statistically significant relationship between PAx, RAC and age with linear regression and age trichotomization analysis but not with PRx and age. 16 Also, in their cohort, biological sex did not have an impact on the cerebrovascular reactivity measures. 16 This cohort had well controlled ICP and CPP values over the course of their intensive care unit (ICU) stay.…”
Section: Introductionmentioning
confidence: 77%
“…16 Also, in their cohort, biological sex did not have an impact on the cerebrovascular reactivity measures. 16 This cohort had well controlled ICP and CPP values over the course of their intensive care unit (ICU) stay. Subsequently, such findings suggested that AMP-based cerebrovascular reactivity indices performed superior to the standard PRx in detecting impaired reactivity in populations with advancing age.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…In cluster #0, the literature largely reported on the management of severe traumatic brain injury (42)(43)(44)(45)(46)(47). The management of traumatic brain injury (TBI) has changed over the past decade; a multimodal approach is now being applied in detecting and treating the pathophysiological derangements.…”
Section: Research Hotspots and Emerging Topicsmentioning
confidence: 99%